ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA BANK BUMN PERIODE 2017-2020 - Dwi Puspita Agustin (Institut Bisnis Muhammadiyah Bekasi, 2021)
Bank as an intermediary institution that is trusted to collect funds and channel them back to the community. In its activities, the bank must demonstrate the level of soundness as required. The bank soundness assessment system is regulated in 13/1/PBI/2011, namely Risk Profile, Good Corporate Governance, Earning and Capital (RGEC). This study aims to analyze the comparison of the soundness of state-owned banks and to determine the assessment of the soundness of banks based on the Risk Profile factor with the ratio of Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), Profitability with the ratio of Return on Assets (ROA) and Capital with Capital Adequacy Ratio (CAR). This research methodology uses secondary data using a period of 4 years, namely 2017-2020. In this study the sample was taken by purposive sampling. In the results of the One Way - Analysis of Variance test on the risk profile and profitability factors, there are significant differences, while the capital factors of the four banks have no significant differences